Discourse of Faá¸Ã¢â€™il al-Qurâ€™an: Muhammad Shadiq's Presentation of the Quran's Privileges in the Book of Qalb al-Qurâ€™an - Deddy Ilyas; Eko Zulfikar (Jurnal Ushuluddin, 2023)
The purpose of this article is to explain Muhammad Shadiq's Qalb al-Qur'an in his work, faá¸Ã¢â€™il al-Qur'an. The inquiries are as follows: What Qur'anic verses are contained in Qalb al-Qur'an? How do the faá¸Ã¢â€™il al-Qur'an forms in Surah al-FÃ¢'tiá¸¥ah verses 4-5 illustrate receiving privileges from the Qur'an? The book of Qalb al-Qur'an by Muhammad Shadiq has a representation of faá¸Ã¢â€™il al-Qur'an that has about 56 features, according to qualitative-descriptive methodologies, informative, and performative approaches from Sam D. Gill. These features consist of a combination of one or two verses that make up the 114 surahs of the Qur'an's qalb (heart). The author shows the fourth and fifth verses in Surah al-FÃ¢â€™tiá¸¥ah as qalb based on several interpretations as evidence of its specialty study. While the fifth verse discusses the responsibilities of a servant who must worship only Allah and always seek His help, the fourth verse discusses Allah's power in the cosmos and how He has the right to reward and hold each of His servants accountable in the hereafter. These two verses are regarded as the qalb in Surah al-FÃ¢â€™tiá¸¥ah because they have a much deeper, more distinctive, and all-encompassing meaning than the other verses